Attention deficit hyperactivity disorder: A pilot study for symptom assessment and diagnosis in children in Chile - Fioravante, Isabella; Lozano-Lozano, José Antonio; Martella, Diana (Frontiers in Psychology, 2022)
Background Attention Deficit Hyperactivity Disorder (ADHD) is one of the most prevalent psychiatric disorders among school-age children and is characterized by varying degrees of inattention, hyperactivity, and impulsivity. Diagnosis, which currently relies on the DSM-V criteria, is complex. This research proposes an integrated procedure for ADHD diagnosis in children, improving the diagnostic process and scientific research on etiopathology. Materials and methods We conducted a clinical report on ADHD diagnosis in children (n = 92) between the ages of 8 and 13, based on the results of the application of different scales to parents of school-age children in Chile. The children were divided into two groups, those with an ADHD diagnosis (n = 44) and those without (n = 48) (24% females). Results The results revealed statistically significant differences between groups for scales EDAH y SDQ-Cas, Conners Comprehensive Behavior Scale, Conners Parent Scale and the criteria according to the DSM-V and its dimensions, with the exception of inattention. Conclusion The findings indicate the importance of appropriate criteria and procedures to establish a diagnosis and implement effective interventions in ADHD.